Biocuration: A New Challenge for the Tunicate Community. Issue 1 (January 2015) - Dauga, Delphine; Christiaen, Lionel; Sasakura, Yasunori; Satou, Yutaka; Yasuo, Hitoyoshi
Summary Biocuration, the field of biology concerned with organizing, representing, checking, and making biological information accessible to both humans and computers, has become an essential part of biological and biomedical research. However, curation increasingly lags behind data generation in funding, development, and recognition. In this work, biocuration efforts accomplished by the community of laboratories working on Tunicata as well as challenges faced were described. Biocuration is essential for the future of scientific research, and that the experience gathered by tunicate community could prove extremely useful to other biologists' communities. genesis 53:132–142, 2015. © 2014 Wiley Periodicals, Inc.